EFFECTS OF METAL INERT GAS WELDING PARAMETERS ON SOME MECHANICAL PROPERTIES OF AUSTENITIC STAINLESS STEEL IN ACIDIC ENVIRONMENT (Nigerian Journal of Technology, 2017)
The purpose of the present study is to investigate the effects of metal inert gas (MIG) welding parameters on the mechanical properties (hardness, tensile and impact) of type 304 austenitic stainless steel (ASS) immersed in 0.5M hydrochloric acid at ambient temperature. The MIG welding was applied to 3mm thick ASS. The dimensions of the samples were 50mm x 15mm x 3mm and 120mm x 15mm x 3mm rectangular bars each for impact, hardness and tensile tests and for immersion in the medium. Design Expert Software, Scanning Electron Microscopy (SEM), Rockwell Hardness Test, Monsanto Tensometer and Izod Impact Test were used to determine the interactions of parameters, microstructural analysis and optimal performances of the parameters respectively. Experimental results indicate that tensile strength increased with increase in welding parameters from 120MN/m2 to 133MN/m2 at speed of 40cm/min and current of 110. when the properties are compared with varying weld parameters adopted in joint’s weld operations, there was a pattern displayed among the weld parameters with C3 (19.7HRA, 203N/mm2 and 19.7J )and C4 (14.9 HRA, 189N/mm2 and 14.9J) consistently coming out as the parameter producing an ASS weld joint with the best mechanical properties of hardness, tensile and impact strength. Surface corrosion deposit composition was analyzed with the SEM paired with energy dispersive spectrometer (EDS) to ascertain microstructural behavior of the material.   http://dx.doi.org/10.4314/njt.v36i3.25